Complementary Characterization of Cu(In, Ga)Se-2 Thin-Film Photovoltaic Cells Using Secondary Ion Mass Spectrometry, Auger Electron Spectroscopy, and Atom Probe Tomography - Jang, Yun Jung; Lee, Jihye; Jeong, Jeung-hyun; Lee, Kang-Bong; Kim, Donghwan; Lee, Yeonhee (AMER SCIENTIFIC PUBLISHERS, 2018)
To enhance the conversion performance of solar cells, a quantitative and depth-resolved elemental analysis of photovoltaic thin films is required. In this study, we determined the average concentration of the major elements (Cu, In, Ga, and Se) in fabricated Cu(In, Ga) Se-2 (CIGS) thin films, using inductively coupled plasma atomic emission spectroscopy, X-ray fluorescence, and wavelengthdispersive electron probe microanalysis. Depth profiling results for CIGS thin films with different cell efficiencies were obtained using secondary ion mass spectrometry and Auger electron spectroscopy to compare the atomic concentrations. Atom probe tomography, a characterization technique with sub-nanometer resolution, was used to obtain three-dimensional elemental mapping and the compositional distribution at the grain boundaries (GBs). GBs are identified by Na increment accompanied by Cu depletion and In enrichment. Segregation of Na atoms along the GB had a beneficial effect on cell performance. Comparative analyses of different CIGS absorber layers using various analytical techniques provide us with understanding of the compositional distributions and structures of high efficiency CIGS thin films in solar cells.
Keywords: QUANTITATIVE-ANALYSIS; HIGH-EFFICIENCY; GROWTH; NA